Optimizing goldfish hatchery of the oranda variety Carassius auratus to improve cultivation performance at BSD fish farm - Iskandar, Andri; Nurfauzi, Eka Haris; Carman, Odang; Indriastuti, Cecilia Eny; Siregar, Budyansah (Politeknik Negeri Sambas, 2024)
The business of cultivating ornamental fish is quite popular because its sales are profitable for cultivators. Ornamental fish also have attractive colors; therefore, many people are interested in this commodity. One ornamental fish commodity that is in great demand is the oranda goldfish Carassius auratus, which has a variety of colors, unique movements, and body shapes. The annual increase in market demand for oranda goldfish reaches 95,000 fish annually, and each year, there is an increase in the production of 3,000 fish of around 3% each year. This study was carried out in an effort to explore technical information on goldfish cultivation so that the information obtained can be disseminated widely and used as a reference source for the community so that it will add value to the benefit of improving sustainable welfare. The results of the study show that the technique of spawning oranda goldfish can be performed naturally using a substrate in the form of a water hyacinth. The average fecundity produced by one female parent oranda goldfish was 6429 eggs, with a presentation hatching rate of 74% and a presentation survival rate of 64%.